Effective lifetime measurements in the B0s → K+K-, B0 → K+π- and B0s → π+K- decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2014)
Measurements of the effective lifetimes in the Bs0→K+K−, B0→K+π− and Bs0→π+K− decays are presented using 1.0 fb−1 of pp collision data collected at a centre-of-mass energy of 7 TeV by the LHCb experiment. The analysis uses a data-driven approach to correct for the decay time acceptance. The measured effective lifetimes areτBs0→K+K−=1.407±0.016(stat)±0.007(syst) ps,τB0→K+π−=1.524±0.011(stat)±0.004(syst) ps,τBs0→π+K−=1.60±0.06(stat)±0.01(syst) ps. This is the most precise determination to date of the effective lifetime in the Bs0→K+K− decay and provides constraints on contributions from physics beyond the Standard Model to the Bs0 mixing phase and the width difference ΔΓs.
Die 0 ist im Titel hochgestellt, das s ist tiefgestellt, die Zeichen + und - sind hochgestellt
Gesehen am 03.09.2020